Application of Location Quotient for Development of Sembalun Tourism Destinations Based on Local Comparative Advantage - Syech Idrus; I Putu Gede; I Ketut Purwata; Si Luh Putu Damayanti; I Ketut Bagiastra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Research dissecting about application of location quotient (LQ) for development of Sembalun Tourism Destinations based on local comparative advantage. The research method used in this study is a survey research method. The population in this study were all core tourism stakeholders in Sembalun District. The technique used to determine the sample in this study is a purposive sampling technique with non-random sampling. The analytical model used in this study is LQ analysis. The results of the study show the potential for diversity of tourism resources from the results of data collection in Sembalun District, which can be grouped as follows: (1)The potential for tourism in the natural environment consisting of (a)land, namely mountains, national parks, hills, lakes, rivers, forests, species flora, fauna, plantations, cultivation, rice fields, vast fields, caves, and waterfalls. (b)water, namely the expanse of the sea, pools of water, and the seabed. (2)The potential for cultural tourism which consists of (a)arts, (b)crafts, (c)livelihood systems, (d)local traditions, (e)culinary arts, (f)cultural festivals, (g)traditional markets, (h)traditional villages, (i)building cultural heritage, (j)cultural heritage objects, (k)cultural heritage sites, (l)traditional equipment and technology systems, (m)cultural heritage areas, (n)intangible culture, and (o)museums. (3)The potential for artificial tourism consists of (a)recreational and entertainment facilities, (b)rest facilities, and (c)recreational and sports facilities. (4)The potential for human resources consisting of (a)experts in the arts, and (b)experts in the field of culture. Based on the results of LQ analysis research, it can be seen that the potential for natural tourism in the form of land is a comparative advantage for tourism development in Sembalun District.